Velocity distributions in a model of traffic flow - de Melo, Alexandre M. S.; Souza, André M. C. (Scientia Plena, 2011)
We use the cellular automaton model in order to describe traffic flow complex variables. More precisely, we study the velocity distributions according to the density of cars. We present the whole spectrum of car velocities using mean-field approximation and numerical simulation. For the maximal high velocity limit of the model both approaches are in very good agreement. However, for maximal intermediate velocity, expected to be qualitatively similar to the experimental data, we have not found much likeness between them.